Provenance change in Carboniferous-early Permian sedimentary successions in the North Qaidam tectonic belt, northern Tibetan Plateau: Implications for the Kunlun oceanic plate subduction process. (December 2022) - Wang, Teng; Zhou, Yanan; He, Weidong; He, Lei; Cheng, Xin; Deng, Xiaohong; Zhang, Dongmeng; Wei, Bitian; Jiang, Nan; Wu, Hanning
Graphical abstract: Highlights: The age of tuff layer from the lower Zhabusagaxiu Formation indicates that the North Qaidam tectonic belt has early Permian sedimentary succession. The major provenance of the North Qaidam tectonic belt evolved southward from the North Qaidam tectonic belt to the East Kunlun Orogen during the Carboniferous to early Permian. Carboniferous to Permian sedimentary successions in the North Qaidam tectonic belt were deposited in a retroarc setting. Abstract: Late Paleozoic sedimentary successions are widespread in the North Qaidam tectonic belt (NQTB), providing an ideal window to constrain the coeval tectonic background of the NQTB to East Kunlun Orogen (EKO). However, little attention has been devoted to these sedimentary-related records. In this study, stratigraphic and detrital zircon U-Pb geochronologic investigations were undertaken on the late Paleozoic successions in the NQTB to reveal multistage tectonic transitions. A weighted mean age of 293 ± 3 Ma was obtained for a tuff sample from the basal Zhabusagaxiu Formation, yielding a first-order time estimate that assigns an early Permian age. Stratigraphic correlation and paleocurrent reconstruction indicate that Carboniferous to early Permian sedimentation in the NQTB took place in a north-dipping neritic environment. Sandstone petrology and detrital zircon geochronology converge to reveal that the major provenance of the NQTB evolved southward from the North Qaidam Orogen in the early Carboniferous, via the EKO and the Qaidam Block in the late Carboniferous, to the EKO in the early Permian. Detrital zircons with crystallization ages of Carboniferous to early Permian in all samples implicate that Carboniferous to Permian magmatism should be common in the EKO. The north-dipping paleogeography and occurrence of syn -depositional magmatic zircons in the provenance further suggest that the tectonic evolution of the NQTB should occur in a retroarc portion, rather than a passive continental margin deepening southwards to the Kunlun Ocean.